Combined training (aerobic plus strength) potentiates a reduction in body fat but demonstrates no difference on the lipid profile in postmenopausal women when compared to aerobic training with a similar training load - Rossi, Fabrício E. [UNESP]; Fortaleza, Ana C S; Neves, Lucas M.; Buonani, Camila; Picolo, Malena R.; Diniz, Tiego A.; Kalva-Filho, Carlos A.; Papoti, Marcelo; Lira, Fabio S.; Freitas Junior, Ismael F. (National Strength & Conditioning Association, 2015)
The aim of this study was to verify the effects of aerobic and combined training on the body composition and lipid profile of obese postmenopausal women and to analyze which of these models is more effective after equalizing the training load. Sixty five postmenopausal women (age=61.0±6.3 years) were divided into three groups: Aerobic Training (AT,n= 15), Combined Training (CT,[strength+aerobic],n=32) and control group (CG,n=18). Their body composition: upper body fat (TF), fat mass (FM), percentage of fat mass and fat free mass (FFM) were estimated by DXA. The lipid profile, total cholesterol, HDL-cholesterol and LDL-cholesterol were assessed. There was a statistically significant difference in the TF (AT= -4.4 %, CT= -4.4%, and CG= 1.0%, p= 0.001) and FFM (AT= 1.7%, CT= 2.6%, and CG= -1.4%, p= 0.0001) between the experimental and the control groups. Regarding the percentage of body fat, there was a statistically significant difference only between the CT and CG groups (AT= -2.8%, CT= -3.9% and CG= 0.31%, p= 0.004). When training loads were equalized, the aerobic and combined training decreased core fat and increased fat-free mass, but only the combined training potentiated a reduction in percentage of body fat in obese postmenopausal women after the training program. HDL-c levels increased in the combined group and the chol/HDL ratio (atherogenic index) decreased in the aerobic group, however, there were no significant differences between the intervention programs. Taken together, both the exercise training programs were effective for improving body composition and inducing an anti-atherogenic status.